Socialism and Identity in the Life and Works of Richard Wright - Gómez, Juan D. (Universidad Pedagógica y Tecnológica de Colombia, 2015)
Richard Wright was a pioneer in American Literature whose relationship with socialism helped to define him as a person and as a writer. The inspiration behind his literary accomplishments and their impact on his contemporaries can be understood by tracing two of the most important themes in his life, socialism and identity. This article describes the evolution of his relationship with socialism in order to better understand the writer and his best known works in their social and political context. This exercise can also help us to gain a clearer understanding of the cultural and social implications of socialist ideology in the United States after the First World War.